A Comparative Study of Antecedents to Contracting Practice in Buyer-Seller Relationships in Egypt and China - A. Hammad, Mahmoud; Ali, Ahmed; Barakat, Ahmed; Dabees, Ahmed; Gamil, Mohamed; Mostafa, Sobhy; Hanafi, Islam (Archives of Business Research, 2020)
The purpose of this study is to analyze the influences of transaction factors on inter-firms relationships in different businesses. The study focuses on the comparison between the Chinese and Egyptian business with regarding to buyer and seller relationships in textile industry in order to find out the differences in buyer-seller relationships between Egypt and China and how the cultural factors influence the contracting practice between these two countries. Therefore, transaction cost analysis (TCA), relational contracting theory (RCT) and resource dependence theory (RDT) would act as the important tools to find out how the business relationship works in different culture background. Combining the three theories, we can conclude the general view about the transaction mechanism in the two countries. Chinese market situation, weak legal system and informal institutions combining with the “guanxi” embedded business environment make the Chinese small firms rely on the relational contracting more than formal contracting. Meanwhile, the high value for law makes Egyptians prefer to formal contracting. The findings highlight the fact that the level of contracting mechanism was found to be more positive in Egypt than in China and was statistically significant. In other words, the Egyptians tend to use the formal transactional mechanisms which emphasize legal conditions and incentive systems, whereas the Chinese prefer the relational mechanisms that govern exchanges through moral control and trust in the relationships between the buyers and suppliers. A hierarchical multiple regression approach employing the OLS regression model was carried out and the findings show that almost 30% of contracting mechanisms can be explained by the model, while the remaining percentage (70%) can be explained by other factors not included in the research model. In addition, the findings revealed that the association between supplier specific investments and contracting becomes significantly more enforced in Egypt than in China when the size of the buying firm increases. Furthermore, contracts have a control effect on buyer-supplier relationships in case of unanticipated eventualities.